155k views
1 vote
Integrate the following problem:


\int {e^(-x) \cdot cos(2x)} \, dx

P.S:
Have fun Lauren (and possibly Kelvy)!

User FileX
by
4.6k points

2 Answers

3 votes

Answer:


\displaystyle (2 \cdot sin2x-cos2x)/(5e^x) + C

Explanation:

The integration by parts formula is:
\displaystyle \int udv = uv - \int vdu

Let's find u, du, dv, and v for
\displaystyle \int e^-^x \cdot cos2x \ dx .


  • u=e^-^x

  • du=-e^-^x dx

  • dv=cos2x \ dx

  • v= (sin2x)/(2)

Plug these values into the IBP formula:


  • \displaystyle \int e^-^x \cdot cos2x \ dx = e^-^x \cdot (sin2x)/(2) - \int (sin2x)/(2) \cdot -e^-^x dx

  • \displaystyle \int e^-^x \cdot cos2x \ dx = (e^-^x sin2x)/(2) - \int (sin2x)/(2) \cdot -e^-^x dx

Now let's evaluate the integral
\displaystyle \int (sin2x)/(2) \cdot -e^-^x dx.

Let's find u, du, dv, and v for this integral:


  • u=-e^-^x

  • du=e^-^x dx

  • dv=(sin2x)/(2) dx

  • v=(-cos2x)/(4)

Plug these values into the IBP formula:


  • \displaystyle \int -e^-^x \cdot (sin2x)/(x)dx = -e^-^x \cdot (-cos2x)/(4) - \int (-cos2x)/(4)\cdot e^-^x dx

Factor 1/4 out of the integral and we are left with the exact same integral from the question.


  • \displaystyle \int -e^-^x \cdot (sin2x)/(x)dx = -e^-^x \cdot (-cos2x)/(4) + (1)/(4) \int cos2x \cdot e^-^x dx

Let's substitute this back into the first IBP equation.


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (e^-^x sin2x)/(2) - \Big [ -e^-^x \cdot (-cos2x)/(4) + (1)/(4) \int cos2x \cdot e^-^x dx \Big ]

Simplify inside the brackets.


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (e^-^x sin2x)/(2) - \Big [ (e^-^x \cdot cos2x)/(4) + (1)/(4) \int cos2x \cdot e^-^x dx \Big ]

Distribute the negative sign into the parentheses.


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (e^-^x sin2x)/(2) - (e^-^x \cdot cos2x)/(4) - (1)/(4) \int cos2x \cdot e^-^x dx

Add the like term to the left side.


  • \displaystyle \int e^-^x \cdot cos2x \ dx + (1)/(4) \int cos2x \cdot e^-^x dx= (e^-^x sin2x)/(2) - (e^-^x \cdot cos2x)/(4)

  • \displaystyle (5)/(4) \int e^-^x \cdot cos2x \ dx = (e^-^x sin2x)/(2) - (e^-^x \cdot cos2x)/(4)

Make the fractions have common denominators.


  • \displaystyle (5)/(4) \int e^-^x \cdot cos2x \ dx = (2e^-^x sin2x)/(4) - (e^-^x \cdot cos2x)/(4)

Simplify this equation.


  • \displaystyle (5)/(4) \int e^-^x \cdot cos2x \ dx = (2e^-^x sin2x - e^-^x cos2x)/(4)

Multiply the right side by the reciprocal of 5/4.


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (2e^-^x sin2x - e^-^x cos2x)/(4) \cdot (4)/(5)

The 4's cancel out and we are left with:


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (2e^-^x sin2x - e^-^x cos2x)/(5)

Factor
e^-^x out of the numerator.


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (e^-^x(2 \cdot sin2x-cos2x))/(5)

Simplify this by using exponential properties.


  • \displaystyle \int e^-^x \cdot cos2x \ dx = (2 \cdot sin2x-cos2x)/(5e^x)

The final answer is
\displaystyle \int e^-^x \cdot cos2x \ dx = (2 \cdot sin2x-cos2x)/(5e^x) + C.

User JoshVarty
by
5.1k points
1 vote

Answer:


\displaystyle\int e^(-x)\cos(2x)\, dx=(2\sin(2x)-\cos(2x))/(5e^x)+C

Explanation:

We would like to integrate the following integral:


\displaystyle \int e^(-x)\cdot \cos(2x)\, dx

Since this is a product of two functions, we can consider using Integration by Parts given by:


\displaystyle \int u\, dv =uv-\int v\, du

So, let’s choose our u and dv. We can choose u base on the following guidelines: LIATE; or, logarithmic, inverse trig., algebraic, trigonometric, and exponential.

Since trigonometric comes before exponential, we will let:


u=\cos(2x)\text{ and } dv=e^(-x)\, dx

By finding the differential of the left and integrating the right, we acquire:


du=-2\sin(2x)\text{ and } v=-e^(-x)

So, our integral becomes:


\displaystyle \int e^(-x)\cdot \cos(2x)\, dx=(\cos(2x))(-e^(-x))-\int (-e^(-x))(-2\sin(2x))\, dx

Simplify:


\displaystyle \int e^(-x)\cdot \cos(2x)\, dx=-e^(-x)\cos(2x)-2\int e^(-x)\sin(2x)\, dx

Since we ended up with another integral of a product of two functions, we can apply integration by parts again. Using the above guidelines, we get that:


u=\sin(2x)\text{ and } dv=e^(-x)\, dx

By finding the differential of the left and integrating the right, we acquire:


du=2\cos(2x)\, dx\text{ and } v=-e^(-x)

This yields:


\displaystyle \int e^(-x)\cdot \cos(2x)\, dx=-e^(-x)\cos(2x)-2\Big[(\sin(2x))(-e^(-x))-\int (-e^(-x))(2\sin(2x))\, dx\Big]

Simplify:


\displaystyle \int e^(-x)\cdot \cos(2x)\, dx=-e^(-x)\cos(2x)-2\Big[-e^(-x)\sin(2x)+2\int e^(-x)\cos(2x)\, dx\Big]

We can distribute:


\displaystyle \int e^(-x)\cdot \cos(2x)\, dx=-e^(-x)\cos(2x)+2e^(-x)\sin(2x)-4\int e^(-x)\cos(2x)\, dx

The integral on the right is the same as our original integral. So, we can isolate it:


\displaystyle \Big(\int e^(-x)\cos(2x)\, dx\Big)+4\Big(\int e^(-x)\cos(2x)\, dx)\Big)=-e^(-x)\cos(2x)+2e^(-x)\sin(2x)

Combine like integrals:


\displaystyle 5 \int e^(-x)\cos(2x)\, dx=-e^(-x)\cos(2x)+2e^(-x)\sin(2x)

We can factor out an e⁻ˣ from the right:


\displaystyle 5\int e^(-x)\cos(2x)\, dx=e^(-x)\Big(-\cos(2x)+2\sin(2x)\Big)

Dividing both sides by 5 yields:


\displaystyle \int e^(-x)\cos(2x)\, dx=(e^(-x))/(5)\Big(-\cos(2x)+2\sin(2x)\Big)

Rewrite. We of course also need the constant of integration. Therefore, our final answer is:


\displaystyle\int e^(-x)\cos(2x)\, dx=(2\sin(2x)-\cos(2x))/(5e^x)+C

User B H
by
6.3k points